Ultrasound probe scratches the pleural surface: revealing the shades of COVID-19 (SARS-CoV-2) pneumonia. Issue 2 (23rd February 2021) - McDowell, Mark; Masih, Izhaq; Cruickshank, Conor; Johnston, Paul
Abstract : We present a case of a patient diagnosed with COVID-19 pneumonia and illustrate the changes observed using thoracic ultrasound alongside disease evolution. The case renders how COVID-19 pneumonia can sonographically correlate with chest radiograph findings and links with the oxygen requirement during different clinical stages of illness. We compare these images as the patient escalates through mild disease on low flow oxygen therapy, moderate disease on high flow oxygen therapy and severe disease requiring mechanical ventilation in the Intensive Care Unit. We then reveal further imaging showing recovery of the disease process. We recommend utilising thoracic ultrasound as it provides clinical effectiveness, ensures patient, staff and equipment safety (in the much-needed personal protective equipment environment) without exposure to radiation. This case report invites clinicians and researchers to share their thoracic ultrasound experience during the COVID-19 pandemic with a wider audience. We hope our observations will increase awareness and give credibility to thoracic ultrasound in future aspects of disease management.